Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.